Kazal-type serine proteinase inhibitors in the midgut of Phlebotomus papatasi - Sigle, Leah T. (Kansas State University, 2011)
Sand flies (Diptera:Psychodidae) are vectors of parasites of the genus Leishmania transmitted to suitable vertebrate host during blood feeding. For blood feeding arthropods, including sand flies, blood meal digestion requires the secretion of inhibitory molecules, such as Kazal-type serine proteinase inhibitors that are involved in preventing the blood from coagulating within the mouthparts and the midgut. Previous studies have identified such molecules in mosquitoes, ticks, and triatomine bugs. Following studies of the midgut transcriptome of Phlebotomus papatasi, the principal vector of Leishmania major, two non-classical Kazal-type serine proteinase inhibitors were identified (PpKzl1 and PpKzl2). We are interested in the role of these proteins as inhibitors of coagulation cascades, in addition to their potential effects on blood digestion in P. papatasi. Ppkzl1 is similar to thrombin and trypsin inhibitors in triatomines and mosquitoes and Ppkzl2 is similar to Kazal-type inhibitors in mosquitoes with unknown function. Analyses of expression profiles indicated that although both transcripts are expressed prior to blood feeding in the midgut of P. papatasi they are tightly regulated by the blood meal. Reverse genetics studies using RNAi-targeted knockdown of PpKzl1 and PpKzl2 by dsRNA injection did not result in a detectable effect on mRNA expression levels. Thus, we expressed a recombinant PpKzl2 in a mammalian expression system (CHO-S free style cells) that was applied to in vitro studies to assess activity against various serine proteinases. Recombinant PpKzl2 inhibited chymotrypsin at nanomolar levels and also inhibited thrombin and trypsin at micromolar levels, suggesting that native PpKzl2 is an active serine proteinase inhibitor and may regulate digestive enzymes and thrombin in the midgut. Leishmania development within the sand fly midgut is faced with several barriers that can severely impact the parasites. For transmission to occur, parasites must be able to overcome these barriers including digestive proteinases, escape from the peritrophic matrix, and midgut attachment. Early stages of Leishmania are susceptible to killing by digestive proteinases in the sand fly midgut. Thus, targeting serine proteinase inhibitors may provide a new strategy to prevent transmission of Leishmania.
Keywords: Sand fly; Kazal domain; Proteinase inhibitor; Blood meal digestion; Midgut; Phlebotomus; Entomology (0353); Molecular Biology (0307)